On the existence of phase transition for one dimensional P-adic countable state Potts model - Mukhamedov, Farrukh (2011)
In the present paper we shall consider countable state p -adic Potts model on Z . A main aim is to establish the existence of the phase transition for the model. In our study, we essentially use one dimensionality of the model. To establish the phase transition we investigation of an infinite-dimensional nonlinear equation. We find a condition on weights to show that the derived equation has two solutions, which yields the existence of the phase transition. Note that it turns out that the finding condition does not depend on values of the prime p , and therefore, an analogous fact is not true when the number of spins is finite.